Genetic admixture patterns in Argentinian Patagonia - Parolin, María Laura (2019)
As in other Latin American populations, Argentinians are the result of the admixtureamongst different continental groups, mainly from America and Europe, and to a lesserextent from Sub-Saharan Africa. However, it is known that the admixture processes did notoccur homogeneously throughout the country. Therefore, considering the importance foranthropological, medical and forensic researches, this study aimed to investigate the populationgenetic structure of the Argentinian Patagonia, through the analysis of 46 ancestryinformative markers, in 433 individuals from five different localities. Overall, in the Patagoniansample, the average individual ancestry was estimated as 35.8% Native American(95% CI: 32.2?39.4%), 62.1% European (58.5?65.7%) and 2.1% African (1.7?2.4%). Comparingthe five localities studied, statistically significant differences were observed for theNative American and European contributions, but not for the African ancestry. The admixtureresults combined with the genealogical information revealed intra-regional variationsthat are consistent with the different geographic origin of the participants and their ancestors.As expected, a high European ancestry was observed for donors with four grandparentsborn in Europe (96.8%) or in the Central region of Argentina (85%). In contrast, theNative American ancestry increased when the four grandparents were born in the North(71%) or in the South (61.9%) regions of the country, or even in Chile (60.5%). In summary,our results showed that differences on continental ancestry contribution have different originsin each region in Patagonia, and even in each locality, highlighting the importance ofknowing the origin of the participants and their ancestors for the correct interpretation andcontextualization of the genetic information.